The Malay Version of the Revised-Suicide Ideation (R-SIS): An Examination of its Psychometric Properties - Halim, Mohd Radzi Tarmizi A; Ibrahim, Norhayati; Abdul Kadir, Nor Ba'yah; Ibrahim, Muhamad Ariff (Knowledge Words Publications, 2021)
The surge prevalence of suicidal behavior among Malaysian attracts attention for prevention and intervention. More recent plates measure suicide behavior per se and predict the tendency of future suicide behavior. However, in Malaysia, such scales were understudied and cause a massive lack of scales and instruments to measure suicidal behavior among Malaysian who was converse in Malay. This study aims to examine the psychometric properties of the translated the Revised-Suicide Ideation Scale (R-SIS) Malay version adapted from the Revised-Suicide Ideation Scale (R-SIS) developed by Rudd (1989). The scales were translated using the back-translation technique once the researcher gets approval for translation from the original author and reviewed by Medical Research Ethics Committee (MREC). The data obtained from a home-to-home survey around Citizen’s Housing Project in Kuala Lumpur and Selangor using purposive random sampling. Overall, a sample of 263 adolescents participated by answering two scales measuring suicidal behavior in this study. The data were analyzed using descriptive statistics, correlation, reliability, and factorial analyses. The results yielded excellent reliability of the Malay translated Revised-Suicide Ideation Scale (R-SIS) and moderate concurrent validity with Beck Suicide Ideation (BIS). Meanwhile, the item-total correlation also shows an excellent discriminant validity. The factorial analysis produces only one factor, and the entire items are loaded into one component. This finding suggests that the Malay version of the Revised-Suicide Ideation Scale (R-SIS) is reliable for measuring suicide ideation and is appropriate for predicting R-SIS Malay version construct among clinical samples.